INDONESIAN – ENGLISH CODE-SWITCHING IN BOY WILLIAM’S YOUTUBE VIDEO ENTITLED “EPISODE 1: LIVY DAN VIOR RIBUT BESAR” - Milana Fitri Italiani; Priska Meilasari (Humaniora Scientia, 2024)
The phenomenon of code-switching occurs in people's speech both through conversation and text. One of them is found in a YouTube video. This study aims to analyze the types and functions of code-switching found in the utterances of host and guest stars in Boy William's YouTube video entitled "Episode 1: Livy dan Vior Ribut Besar". In conducting this research, the methodology chosen is a qualitative descriptive method that analyzes the type and function of code-switching by watching the video multiple times, taking notes, and classifying the types and functions of code-switching. The theory used in this research was proposed by Poplack (1980) to analyze the different types of code-switching. While the theory proposed by Apple & Muysken (2005) is used to analyze the function of code-switching. The results showed that there were 3 types of code-switching found in the host and guest star's conversations in the video. The types of code-switching consist of tag switching, intra-sentential switching, and inter-sentential switching. All types of code-switching found amounted to 144 data with intra-sentence switching being the most dominant type with 121 data, and the least dominant type is tag switching with only 6 data. In this study, there are five functions of code-switching. The most dominant function is the referential function with 48 data and the least dominant function is a directive function with only 1 data.